Dimensioning of a sustainable system for the treatment of domestic sewage in a residential condominium of the municipal of Caçador/SC - Campos, Roger Francisco Ferreira de; Alves, Djanecler; Borga, Tiago; García, Santiago Sánchez (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Urban population growth, when not properly managed, has a significant negative environmental impact on the environment. Among these impacts, one of the main mitigating factors in environmental pollution is domestic, commercial and industrial sanitary sewage. Therefore, the present work has the objective of developing a sustainable system of treatment of domestic sewage, through the design of a treatment system composed of septic tank, biological filter and root zone tank for a horizontal residential condominium of the municipality of Caçador/SC. With the scaling of sustai-nable phytoremediation systems, such as septic tank aftertreatment and biological filtering is a viable alternative, due to the environmental benefit of the implantation, since the root zone treatment systems assist in the purification of the effluents, to later obtain drainage of the municipality. Thus, the present study seeks to have a sustainable method for condominiums, buildings and residences in rural areas, but mainly in urban areas.